2006
DOI: 10.1007/s11060-006-9231-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival and quality of life after hypofractionated stereotactic radiotherapy for recurrent malignant glioma

Abstract: Hypofractionated stereotactic radiotherapy with 5 x 7 Gy of recurrent high grade glioma is an effective treatment that helps to maintain quality of life for an acceptable period, comparable to the results obtained with current chemotherapy schedules. Combined approaches of radiotherapy, chemotherapy and other targeted therapies deserve further inverstigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…During the last decade, there has been an increased interest in fractionated stereotactic reirradiation as a palliative measure for patients with recurrent GBM, in combination with chemotherapy and reresection, if possible [9,16,21,22]. In this study, we found a median OS of 27 months estimated from the first diagnosis.…”
Section: Resultsmentioning
confidence: 53%
“…During the last decade, there has been an increased interest in fractionated stereotactic reirradiation as a palliative measure for patients with recurrent GBM, in combination with chemotherapy and reresection, if possible [9,16,21,22]. In this study, we found a median OS of 27 months estimated from the first diagnosis.…”
Section: Resultsmentioning
confidence: 53%
“…The effect of reirradiation, specifically on HRQOL, was evaluated in a small study with a median follow-up of 9 months [49]. The majority of patients (80%) judged their general health status after reirradiation to be stable or even improved, compared with before treatment; in 20% of patients, their perceived general health status declined.…”
Section: Effect Of Radiotherapy On Hrqolmentioning
confidence: 99%
“…For recurrent high-grade glioma, radiochemotherapy may further increase the treatment efficiency. There are many studies delivering hypofractionated SRS with doses between 3 and 5 Gy per fraction for local relapse after prior conventional radiotherapy doses of 60 Gy [9,14,15,18]. The resulting overall survival after hypofractionated stereotactic re-irradiation ranges from 10 months for high-grade tumors to 20 months for low-grade lesions.…”
Section: Brain Gliomamentioning
confidence: 99%